2011
DOI: 10.1007/s13280-011-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altered Offshore Food Webs on Coastal Ecosystems Emphasize the Need for Cross-Ecosystem Management

Abstract: By mainly targeting larger predatory fish, commercial fisheries have indirectly promoted rapid increases in densities of their prey; smaller predatory fish like sprat, stickleback and gobies. This process, known as mesopredator release, has effectively transformed many marine offshore basins into mesopredator-dominated ecosystems. In this article, we discuss recent indications of trophic cascades on the Atlantic and Baltic coasts of Sweden, where increased abundances of mesopredatory fish are linked to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
144
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 43 publications
7
144
0
2
Order By: Relevance
“…In most vegetated coastal ecosystems, algal-feeding mesograzers play a key role in controlling ephemeral algae biomass, thereby facilitating habitat-forming perennial macrovegetation, such as the eelgrass Z. marina (39,40). Suppression or removal of mesograzers, for example, by trophic cascades induced by overfishing of large predators, can flip these ecosystems to bottom-up stimulation (11,12,39,40). We observed this same pattern; mesograzers affected the balance between bottom-up and top-down regulation by (i) feeding on epiphytic and floating macroalgae, leading to increased light penetration; and (ii) preying upon smaller sediment-associated fauna that in turn fed on the benthic microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…In most vegetated coastal ecosystems, algal-feeding mesograzers play a key role in controlling ephemeral algae biomass, thereby facilitating habitat-forming perennial macrovegetation, such as the eelgrass Z. marina (39,40). Suppression or removal of mesograzers, for example, by trophic cascades induced by overfishing of large predators, can flip these ecosystems to bottom-up stimulation (11,12,39,40). We observed this same pattern; mesograzers affected the balance between bottom-up and top-down regulation by (i) feeding on epiphytic and floating macroalgae, leading to increased light penetration; and (ii) preying upon smaller sediment-associated fauna that in turn fed on the benthic microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships for these species were non-linear and indicated that habitat availability becomes particularly important in areas where availability is low, such as in outer archipelago areas. In the long term, even relatively small local losses may have negative effects on populations, impacting both ecosystem functioning and the sustainability of fisheries (Eriksson et al 2011). Although it is difficult to assess the potential impact of a single development project, it is important for managers both to know the shoreline development status and trends in their area to appreciate the potential cumulative effects of constructions on fish reproduction and overall biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Such a feedback could be generated by shoreline constructions by reducing vegetation cover (Sandström et al 2005), leading to a lower quality of the reproduction habitats needed to maintain population sizes . Consequently, as the abundance of large predatory fish is reduced, so is the top-down control of epiphytic algae (Eriksson et al 2011), which, if abundant, potentially further reduce the quality of the reproduction habitat by limiting vegetation cover, leading to a negative spiral.…”
Section: Discussionmentioning
confidence: 99%
“…In areas where populations of coastal predatory fish such as perch (Perca fluviatilis) and pike (Esox lucius) are weak, mesopredatory fish, such as the three-spined stickleback (Gasterosteus aculeatus), are present in high numbers (Eriksson et al 2009, Byström et al 2015. These mesopredators can have substantial impacts on the community of invertebrate grazers, reducing their numbers and hence the grazing pressure on algae, ultimately leading to eutrophication symptoms and habitat changes with blooms of ephemeral filamentous algae (Korpinen and Jormalainen 2007, Baden et al 2010, Sieben et al 2011, Östman et al 2016. Sticklebacks may also affect the egg and larval stages of many species of predatory fish negatively, further emphasizing this problem Byström et al 2015).…”
mentioning
confidence: 99%
“…the USA and Canada. In these countries, management of EFH is regulated by legal acts.Healthy vegetated habitats are needed for the reproduction of many coastal fishes (Rangeley and Kramer 1995, Stål et al 2007, Snickars et al 2010, Seitz et al 2014, while strong populations of predatory fish may support habitat-forming vegetation through maintaining trophic cascades (Norderhaug et al 2005, Moksnes et al 2008, Newcombe and Taylor 2010, Eriksson et al 2011, Svensson et al 2012. To increase the awareness of the benefits of integrating management of fisheries and habitat, the scientific community could contribute in many ways.…”
mentioning
confidence: 99%